Influence of CO2 on the Electrical Conductivity and Streaming Potential of Carbonate Rocks. Issue 10 (2nd October 2019) - Cherubini, A.; Garcia, B.; Cerepi, A.; Revil, A.
Abstract: Minimally intrusive geophysical methods are required to monitor CO2 leakages from underground storage reservoirs. We investigate the impact of gaseous CO2 on both electrical conductivity and electrokinetic properties of two limestones during their drainage. These data are contrasted with measurements performed on one clay‐free sandstone. The initial NaCl brine concentrations before drainage (from 8.5 to 17.1 mMol/L) correspond to the limit between freshwater and slightly brackish water. These values are representative to saturated brine formations inside which CO2 can be stored. Using these water salinities, the surface conductivity of the samples represents less than 5% of the overall electrical conductivity. A CO2 release leads to an increase of the electrical conductivity of the rock during drainage in limestones and no change in sandstone. This increase in the electrical conductivity is due to the dissolution of calcite with the concomitant release of Ca 2+ and HCO3 − in the pore water. It is not due to the CO2 dissociation in the pore water in the pore pressure range 0–0.5 MPa and at a temperature of T = 20 °C. The measurements of the streaming potential show a substantial decrease of the streaming potential coupling coefficient and zeta potential magnitudes after a CO2 release in carbonates. This observation is explained by the increase of the ionic strength of the pore water in the course of the experiment. This change can be used, in turn, to determine calcite dissolution rates from the measurement of the electrokinetic properties. Key Points: The dissolution of calcite leads to a decrease of the magnitude of the streaming potential coupling coefficient The pore water conductivity is dominated by the calcite dissolution in carbonates Calcite dissolution rates calculated from streaming potential measurements are consistent with PHREEQC simulations